(untitled) (Fiep Bulletin - online, 2016)
The purpose of this research was to identify and compare the psychomotor level with the body mass index and fat percentage of children aged 8 to 10 years. The study sample consisted of 400 schoolchildren aged 8 to 10 yearsfrom ten schools from public and private institutions in the municipality of Rio de Janeiro, being 40 children in each school of both genders. The instruments used in this study were the Psychomotor Battery, Vítor da Fonseca (1995), which presents an analysis protocol of psychomotor profile by evaluating seven psychomotor factors (Tonicity and Balancing, Lateralization, the Body Concept and Spatial-Temporal Structure, Global praxis and Fine Praxis;. the Body Mass Index Protocol proposed by OMS (2007) and the Protocol of Percent Body FatRating proposed by Lohman (1997) – Triceps Skinfold and subscapular. The results revealed in the survey showed superiority in Psychomotor Level in older children aged 10 years. The data on BMI and body fat percentage, showed general level close to normal, with some cases of overweight. When compared with the psychomotor level, BMI data and Body Fat Percentage did not show considerable correlation. The conclusive research data suggests that Physical Education have as a major goal the maturing of the psychomotor level, especially in middle childhood and preadolescence, as the control of body mass index and fat percentage close the level of normalcy.